A Systematic Review of Deep Learning for Intelligent Transportation Systems with Analysis and Perspectives - Hendrawan, Aria; Gernowo, Rahmat; Nurhayati, Oky Dwi; Dewi, Christine (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
This study presents a systematic review of deep learning for intelligent transportation systems. Statistics are used to find the most cited articles, and the number of articles and quotes are used to find the most productive and influential authors, institutions, and countries or regions. Key topics and patterns of change are discovered using the authors’ keywords, and the most common issues and themes are revealed using flow maps and showing the corresponding trends. A co-occurrence keyword network is also developed to present the research landscape and hotspots in the field. The results explain how publications have changed over the past seven years. Researchers can use this study to have a deeper understanding of the current state and future trends in the role of deep learning in intelligent transportation systems.